PENGARUH KINERJA LINGKUNGAN, BIAYA LINGKUNGAN & UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA (Studi pada Perusahaan Sektor Pertambangan Periode 2018-2019) - Sayidah Maryam Sinosi; Nirwani Nirwani; Kartini Kartini; Yohanis Rura (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this research is to find out how the influence of environmental performance, environmental costs and company size on the company's financial performance. The population of this study is all mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2019 period. This research is on the official website on the Indonesia Stock Exchange, namely on the web www.idx.co.id. The results of this study indicate that environmental performance, environmental costs and firm size simultaneously affect financial performance. Environmental performance and company size have a positive effect on financial performance, while environmental costs have no effect on financial performance.